Wireless System for Sleeper Vibrations Measurement - Ljiljana M. Brajovic; Miodrag Malovic; Zdenka Popovic; Luka Lazarevic (Communications - Scientific letters of the University of Zilina, 2014)
This paper describes testing of a wireless technique for measuring the actual sleeper vibrations and determination of their dynamic deflection based on the experimentally acquired acceleration data. Practical measurements of sleeper vibrations and calculation of displacements (deflections) along the track provide insight into the actual condition of layers below sleepers. The main goal was to develop the equipment for structural health monitoring as a basis for the track maintenance management.